Covid-19 and Diaguita communities: structural inequalities and (inter)community strategies in the Santa María department (Catamarca, Argentina) - Luciana García Guerreiro (Salud Colectiva)
The aim was to investigate and analyze the social, health, and economic impact of the Covid-19 pandemic on Indigenous communities in the province of Catamarca (Argentina), while also identifying the various strategies developed by these communities to address this phenomenon. The research was conducted between December 2021 and December 2022, with an exploratory nature and a predominantly qualitative methodological design. During the fieldwork, 15 in-depth interviews were conducted with community authorities, community members, territorial technicians, and health workers, complemented by 30 structured interviews with individuals from different communities in the Santa María Department. Although tensions between the official health system and Indigenous communities (with their worldviews and ancestral practices) are evident, the importance of community self-management and territorial control over Indigenous organizational processes is also observed in health prevention and care actions, as well as in establishing dialogues and negotiations with local health authorities regarding the implementation of measures in the territories.